Credit Union Models in Poland and USA in Comparative Perspective - Migdalski, Maksymilian (PRAWO i WIĘŹ, 2024)
The article introduces the concept of two models of credit unions: American and Polish. The distinction is the result of a comparative analysis of selected aspects of the functioning of credit unions in Poland and the USA, such as the nature, interpretation of the common bond, scope of activities, organizational structure or supervision. The article highlights the peculiarities of each credit union system, which allow to distinguish two models of functioning of these institutions. The paper presents postulates focused on efforts to increase the competitiveness and efficiency of the credit union system in Poland.